Pelatihan Pembuatan Ekoenzim dan Keranjang Takakura untuk Pengolahan Sampah Dapur - Laksmindra Fitria; Chalivya Aska Rarafifi; Putri Dian Islami; Albert Lonardo; Tantri Ajeng Salma Salsabila; Enggal Prayogo (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
This program aimed to provide training on processing kitchen waste through Ecoenzyme and Takakura composting methods with the target of members of farmer women's group. Survey revealed that >88% of residents lack of knowledge of kitchen waste processing methods and were interested to learn. Training activities including tutorials, practices, and assistance in making Ecoenzyme and Takakura compost for three months. Results were five Ecoenzyme jars with 80% success rate and five Takakura baskets with 80% success rate. Both products were tested on several plants for experimentation, which will later be applied by residents independently in their yards.